One-Pot Three Component Synthesis of Highly Functionalized Novel 1,8-Naphthyridine Derivatives from Substituted 2-Aminopyridines, Aldehydes and Malononitrile - Yaqub, Muhammad; Naveed, Muhammad Kashif; Riaz, Muhammad Tariq; Perveen, Ruqayia; Batool, Javaria; Arif, Nadia; Yaseen, Muhammad (Asian Journal of Chemistry, 2015)
Protocol for one-pot three component cascade synthesis was planned to achieve the highly functionalized novel 1,8-naphthyridine derivatives from readily available starting material. Substituted aldehydes and malononitrile were refluxed in THF followed by the addition of substituted 2-aminopyridine to obtain highly functionalized novel 1-8-naphthyridine (12a-12x), in good to excellent yields. The structures of the newly synthesized 1,8-naphthyridine derivatives have been established on the basis of analytical (C, H, N) and spectroscopic (1H NMR and 13C NMR) data. These fully functionalized heterocycles would be employed as versatile synthons for further chemical transformation and eventually, screened for biological studies.